Molecular Genomic Assessment Using a Blood-based mRNA Signature (NETest) is Cost-effective and Predicts Neuroendocrine Tumor Recurrence With 94% Accuracy. Issue 3 (September 2021) - Modlin, Irvin M.; Kidd, Mark; Frilling, Andrea; Falconi, Massimo; Filosso, Pier Luigi; Malczewska, Anna; Kitz, Alexandra
Abstract : Introduction: Identification of residual disease after neuroendocrine tumor (NET) resection is critical for management. Post-surgery imaging is insensitive, expensive, and current biomarkers ineffective. We evaluated whether the NETest, a multigene liquid biopsy blood biomarker, correlated with surgical resection and could predict recurrence. Methods: Multicenter evaluation of NET resections over 24 months ( n = 103): 47 pancreas, 26 small bowel, 26 lung, 2 appendix, 1 duodenum, 1 stomach. Surgery: R0 (83), R1/R2 (20). One millilitre of blood was collected at D0 and posroperative day (POD) 30. Transcript quantification by polymerase chain reaction (normal: ⩽20), CgA by NEOLISA (normal ⩽108 ng/mL). Standard-of-care (SoC) follow-up costs were calculated and compared to POD30 NETest-stratification approach. Analyses: Wilcoxon-paired test, Chi-square test. Results: D0 biomarkers: NETest: 103 of 103 (100%)-positive, whereas 23 of 103 (22%) were CgA-positive (Chi-square = 78, P < 0.0001). In the R0 group, the NETest decreased 59 ± 28 to 26 ± 23 ( P < 0.0001); 36% (30/83) remained elevated. No significant decrease was evident for CgA. In the R1/R2 group the NETest decreased but 100% remained elevated. CgA levels did not decrease. An elevated POD30 NETest was present in R0 and 25 (83%) developed radiological recurrences. Normal score R0 s ( n = 53) did not develop recurrence (Chi-square = 56, P < 0.0001). Recurrence prediction was 94% accurate with the NETest. Cost evaluation: Using the NETest to stratify postoperative imaging resulted in a cost-savings of 42%. Conclusion: NETest diagnosis is more accurate than CgA (100% vs 22%). Surgery significantly decreased NETest. An elevated POD30 NETest predicted recurrence with 94% accuracy and post-surgical POD30 NETest follow-up stratification decreased costs by 42%. CgA had no surgical utility. Further studies would define the accuracy and cost-effectiveness of the NETest in the detection of postoperative recurrent disease. Abstract : Supplemental Digital Content is available in the text